2017
DOI: 10.2131/jts.42.797
|View full text |Cite
|
Sign up to set email alerts
|

Actual consumption amount of personal care products reflecting Japanese cosmetic habits

Abstract: -Safety assessments of cosmetics are carried out by identifying possible harmful effects of substances in cosmetic products and assessing the exposure to products containing these substances. The present study provided data on the amounts of cosmetic products consumed in Japan to enhance and complement the existing data from Europe and the United States, i.e., the West. The outcomes of this study increase the accuracy of exposure assessments and enable more sophisticated risk assessment as a part of the safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
14
2
Order By: Relevance
“…Realistic evaluation of chemical permeation can be attained when conditions closely simulating actual use conditions are employed [119]. The use of a finite dose and the manner of formulation application (in membrane) must be reflective of actual in-use conditions (e.g., layered application, defined sequence).…”
Section: Determining Permeation Of Alcohol and Solvent/cosmetic Actimentioning
confidence: 99%
“…Realistic evaluation of chemical permeation can be attained when conditions closely simulating actual use conditions are employed [119]. The use of a finite dose and the manner of formulation application (in membrane) must be reflective of actual in-use conditions (e.g., layered application, defined sequence).…”
Section: Determining Permeation Of Alcohol and Solvent/cosmetic Actimentioning
confidence: 99%
“…[8][9][10]12,28 One previous study on the quantities of various cosmetic products actually applied by Japanese individuals suggested that each person applied 0.82 g sunscreen and 0.138 g liquid foundation per application on average. 16 In our study, the real-use conditions of layering were set as reduced application dose as well, and we simulated the use of even lower concentrations of makeup products than sunscreen, guided by our small-scale pretest and previous studies. 16,28 The use of less makeup than sunscreen may be due to the easily observed change in facial color upon application of makeup products.…”
Section: Discussionmentioning
confidence: 99%
“…We set up two common facial makeup routines: (a) consecutive application of sunscreen and cushion-type foundation and (b) consecutive application of sunscreen, liquid foundation, and compact powder. The amount of each product applied was chosen to reflect real-life conditions, based on the results of a previous study 16 and the results of a small-scale pretest in which we measured the weight of a product before and after application. The quantities of products used were divided by the covered skin area to determine the appropriate amount of product to apply per area of skin for the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cosmetics is associated with a variety of social outcomes, ranging from perception of physical attractiveness to evaluation of expected job performance (Bartles, 2019). However, in many countries, as well as in Lithuania, there is anxiety about the impact of cosmetic products on consumer health in the society (Malinauskienė, 2015;Cho et al, 2017;Kirchhof & Gannes, 2013;Yamaguchi et al, 2017). Lithuania is not among the leaders of cosmetic countries, producing and dominating in the export of products to other countries of the world, but it has a lot of small manufacturers of cosmetics.…”
Section: Introductionmentioning
confidence: 99%